Nonlinear Numerical Simulation to Thermo-elastic-plastic Creep Constitutive Equation for Concrete Subjected to Fire - Zhenqing Wang; Dalei Zhu; Mu Qiao; Yulai Han (2010 Third International Joint Conference on Computational Sciences and Optimization, 2010)
In order to discuss the material behavior of concrete subjected to fire, based on elastic-plastic theories, considering the variation of material properties with temperature, the general incremental thermo-elastic-plastic creep constitutive equation is derived in consideration of temperature and creep deformation. According to Drucker-Prager yield rules, the incremental thermo- elastic-plastic creep constitutive equations for concrete are obtained. The algorithms of backward Euler integration and implicit integration are adopted for the numerical simulation to the constitutive equation. It is concluded from the numerical results that the creep strain of concrete at elevated temperature can not be ignored. The correctness and applicability of the constitutive equations are verified by the test results of relevant reference.